Tracking of the origin of recurrent mutations of the BRCA1 and BRCA2 genes in the North-East of Italy and improved mutation analysis strategy. Issue 1 (December 2016) - Cini, Giulia; Mezzavilla, Massimo; Della Puppa, Lara; Cupelli, Elisa; Fornasin, Alessio; D'Elia, Angela; Dolcetti, Riccardo; Damante, Giuseppe; Bertok, Sara; Miolo, Gianmaria; Maestro, Roberta; de Paoli, Paolo; et al.
Abstract Background About 20 % of hereditary breast cancers are caused by mutations inBRCA1 andBRCA2 genes. SinceBRCA1 andBRCA2 mutations may be spread throughout the gene, genetic testing is usually performed by direct sequencing of entire coding regions. In some populations, especially if relatively isolated, a few number of recurrent mutations is reported, sometimes caused by founder effect. Methods BRCA1 andBRCA 2 screening for mutations was carried out on 1114 breast and/or ovarian cancer patients complying with the eligibility criteria for BRCA testing. Haplotype analysis was performed on the probands carrying recurrent mutations and their relatives, using two sets of microsatellite markers covering theBRCA1 (D17S588, D17S806, D17S902, D17S1325, D17S855, D17S1328, D17S800, and D17S250) andBRCA2 (D13S220, D13S267, D13S171, D13S1701, D13S1698, D13S260, D13S290, D13S1246)loci . The DMLE + 2.2 software was used to estimate the age ofBRCA1 c.676delT andBRCA2 c.7806-2A > G. A multiplex PCR and two different primer extension assays were optimized and used for genotyping the recurrent mutations of the two genes. Results In the time frame of almost 20 years of genetic testing, we have found that fiveBRCA1 and threeBRCA2 mutations are recurrent in a substantial subset of carriers from North-East Italy and neighboring Istria, where they represent more than 50 % of all mutations. Microsatellite analyses identified a common haplotype of different length for each mutation. Age estimation ofBRCA1 c.676delT andBRCA2 c.7806-2A > G mutations revealed that they arose in the Friuli Venezia Giulia area about 86 and 94 generations ago, respectively. Suggestion of an association betweenBRCA2 c.7806-2A > G and risk of breast cancer in males has emerged. Finally, we developed a simple and efficient pre-screeening test, performing an in-house primer extension SNaPshot® assay for the rapid identification of the eight recurrent mutations. Conclusions Proofs of common ancestry has been obtained for the eight recurrent mutations. The observed genotype-phenotype correlation and the proposed rapid mutation detection strategy could improve the clinical management of breast and ovarian patients in North-East of Italy and neighboring geographic areas.